PTH-103 Clinician Confidence in Stratifying Risk in Primary Biliary Cirrhosis - A UK-PBC Survey. (17th August 2016) - Corrigan, M; Vale, L; Coughlan, D; Jones, D; Hirschfield, G
Abstract : Introduction: Primary biliary cirrhosis or Primary biliary cholangitis (PBC) has only one licensed therapy, ursodeoxycholic acid (UDCA). Assessment of biochemical response to UDCA allows identification of patients who are at high risk of disease progression and would be suitable for trials and emerging therapies. The aim of this survey was to determine current understanding of UDCA response criteria amongst clinicians practicing in the UK. Methods: An online survey of clinical practice was created by UK-PBC and distributed to clinicians via the British Society of Gastroenterology (BSG) and British Association for the Study of the Liver (BASL) mailing list and newsletters. The survey was carried out between April and June 2015. Questions covered diagnosis and management of the condition with four questions specifically covering UDCA response assessment. Statistical analysis was performed using GraphPad software. Chi squared testing as used to compare groups. Results: A total of 206 responses were received. Respondents came from a variety of clinical backgrounds – consultant in a tertiary hospital – 14 (7%), consultant hepatologists in non tertiary centres – 32 (15.5%), consultant gastroenterologists – 75 (36.4%), trainees – 78 (37.9%), others including specialist nurses – 7 (3.4%). Whilst 90% of respondents reported routine use of UDCA in clinical practice, only 20% reported that they always assessed UDCA response once the patient had been on treatment for 12 months. 50% never formally assessed treatment response. Looking at rates of assessment of UDCA response between specialist groups: 64% of gastroenterologists and 47% of trainees never assessed response compared to 25% of non-tertiary hepatologists and 14% of tertiary hepatologists. The number of patients seen appeared to affect rates of UDCA response assessment: 64% of those who saw fewer than 10 patients per year never assessed response compared to 10% of those who saw more than 50 patients per year. 40% of respondents reported themselves to be " not at all confident" in assessing response with 58% stating they were unaware of response criteria and 27% were unsure of the best criteria to use. Conclusion: The majority of patients with PBC are managed by non-specialists outside of tertiary centres many of whom see low volumes of patients with this condition. The application of emerging therapies for patients with PBC requires appropriate use of risk stratification tools in routine clinical practice. Our results demonstrate gaps in knowledge and confidence amongst non-specialists. Implementing a stratified approach to management requires these gaps to be addressed. Disclosure of Interest: None Declared